Interactive surface in the PapD chaperone cleft is conserved in pilus chaperone superfamily and essential in subunit recognition and assembly. - Slonim, L N (1992)
The assembly of adhesive pili in Gram-negative bacteria is modulated by specialized periplasmic chaperone systems. PapD is the prototype member of the superfamily of periplasmic pilus chaperones. Previously, the alignment of chaperone sequences superimposed on the three dimensional structure of PapD revealed the presence of invariant, conserved and variable amino acids. Representative residues that protruded into the PapD cleft were targeted for site directed mutagenesis to investigate the pilus protein binding site of the chaperone. The ability of PapD to bind to fiber-forming pilus subunit proteins to prevent their participation in misassembly interactions depended on the invariant, solvent-exposed arginine-8 (R8) cleft residue. This residue was also essential for the interaction between PapD and a minor pilus adaptor protein. A mutation in the conserved methionine-172 (M172) cleft residue abolished PapD function when this mutant protein was expressed below a critical threshold level. In contrast, radical changes in the variable residue glutamic acid-167 (E167) had little or no effect on PapD function. These studies provide the first molecular details of how a periplasmic pilus chaperone binds to nascently translocated pilus subunits to guide their assembly into adhesive pili.